Cost-Effectiveness Analysis of Oral Antidiabetic Monotherapy with Metformin and Glimepiride in Diabetes Mellitus at Bahteramas Hospital - Pusmarani, Jastria; Apriani, Rini; Himaniarwati, Himaniarwati; Baco, Julianas; Azlimin, Azlimin (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Healthcare expenditure due to diabetes mellitus in Indonesia reaches approximately US$143 per person. The largest portion of this cost is attributed to medications. Therefore, ensuring the cost-efficiency and effectiveness of drug use is critically important. This study aims to determine and analyze the cost-effectiveness of antidiabetic drug therapy in patients with type 2 diabetes mellitus in the outpatient department of Bahteramas Hospital in Southeast Sulawesi Province. Descriptive methods and quantitative analysis of medical record data from Type 2 diabetes mellitus (DM) patients and treatment costs at Bahteramas Hospital in 2023. A total of 61 patients were included in the study based on the inclusion criteria. Based on the average cost-effectiveness ratio (ACER), glimepiride was more efficient, with a value of IDR 18,389, compared to metformin, which had an ACER of IDR 25,405. However, based on the incremental cost-effectiveness ratio (ICER), metformin was more cost-effective, with a value of IDR 50,070. While the biguanide group (metformin) appears more cost-effective than the sulfonylurea group (glimepiride) based on ICER, the overall findings indicate that, based on ACER, glimepiride (sulfonylurea) is more cost-effective. Therefore, glimepiride can be recommended as a single oral antidiabetic therapy at Bahteramas Hospital.